A digital hysteresis control method for three-level grid-tie inverter based on online prediction of sampling time without inductance - Shulin, Cai; Daxi, Li; Siyu, Shao; Xinyu, Yang; Qiang, Zhang; Peiyuan, Cheng (Frontiers in Energy Research, 2024)
This article proposed a digital hysteresis control method for three-level grid-tie inverter based on online prediction of sampling time without inductance. The proposed method eliminated the effect on the control accuracy of the inductor changing with the current in the LCL filter of the grid-tie inverter, and reduced the equivalent sampling rate in digital hysteresis control by predicting and correcting the sample time. The simulations and experimental tests confirm the effectiveness of the proposed digital hysteresis control method.